1999
DOI: 10.1523/jneurosci.19-14-06079.1999
|View full text |Cite
|
Sign up to set email alerts
|

Shunting versus Inactivation: Analysis of Presynaptic Inhibitory Mechanisms in Primary Afferents of the Crayfish

Abstract: Primary afferent depolarizations (PADs) are associated with presynaptic inhibition in both vertebrates and invertebrates. In the present study, we have used both anatomical and electrophysiological techniques to analyze the relative importance of shunting mechanisms versus sodium channel inactivation in mediating the decrease of action potential amplitude, and thereby presynaptic inhibition. Experiments were performed in sensory afferents of a stretch receptor in an in vitro preparation of the crayfish. Lucife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 28 publications
4
108
0
Order By: Relevance
“…It is not well understood why there is such a different effect in different cells. Inactivation of Na channels and increased membrane conductance (shunting) contribute to the inhibitory effect in at least some of the mechanosensory neurons (Cattaert and El Manira 1999;French et al 2006), but other ionic mechanisms have also been suggested (Graham and Redman 1994;Kriz et al 1974;Walmsley et al 1995). In the present study, we demonstrated that a slow voltage-activated Na ϩ current contributes to the depolarization resulting from activation of GABA A receptors in spider VS-3 mechanosensory neurons.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…It is not well understood why there is such a different effect in different cells. Inactivation of Na channels and increased membrane conductance (shunting) contribute to the inhibitory effect in at least some of the mechanosensory neurons (Cattaert and El Manira 1999;French et al 2006), but other ionic mechanisms have also been suggested (Graham and Redman 1994;Kriz et al 1974;Walmsley et al 1995). In the present study, we demonstrated that a slow voltage-activated Na ϩ current contributes to the depolarization resulting from activation of GABA A receptors in spider VS-3 mechanosensory neurons.…”
Section: Discussionsupporting
confidence: 68%
“…Although the increase in Cl Ϫ conductance in response to GABA A -receptor activation is generally accepted as the primary mechanism behind the primary afferent depolarization, there is still controversy about the ionic mechanism that leads to inhibition. Previous results in the VS-3 neurons indicated that inactivation of voltage-gated Na channels during GABA-mediated depolarization and membrane "shunting" can both cause inhibition Panek et al 2001), agreeing with results in many other neurons (e.g., AlvarezLeefmans et al 1998;Cattaert and El Manira 1999). Kritz et al (1974) suggested that in the spinal cord accumulation of K ϩ in the extracellular space could also produce depolarization leading to inhibition.…”
Section: Ionic Mechanism Of Presynaptic Inhibitionsupporting
confidence: 64%
See 1 more Smart Citation
“…Membrane depolarization and increased conductance (shunting) have been previously shown to contribute to the inhibitory effects of GABA, including presynaptic inhibition, on primary afferent mechanosensory neurons in many vertebrate and invertebrate preparations (Cattaert and El Manira 1999;Rudomin and Schmidt 1999). Since similar depolarization and shunting occur in the peripheral parts of spider VS-3 neurons and have previously been shown to contribute to the inhibitory effect (French et al 2006;Panek et al 2002), we asked whether they could also explain the increase in sensitivity when the neurons are stimulated with random signals.…”
Section: Depolarization Shunting and Gaba-induced Excitationmentioning
confidence: 99%
“…Presynaptic inhibition is produced by spinal interneurons with GABAergic axo-axonic synapses on primary afferent terminals (Eccles et al, 1962;Rudomin and Schmidt, 1999;Hughes et al, 2005). With GABAergic activation, Cl Ϫ anions escape the negative intra-axonal environment, thus producing a primary afferent depolarization (PAD) (Eccles et al, 1963;Nicoll and Alger, 1979;Cattaert and El Manira, 1999).…”
Section: Introductionmentioning
confidence: 99%